Reprodução induzida e desenvolvimento inicial do Jundiá Leiarius marmoratus (PISCES: SILURIDAE) - Mira López, Tatiana María [UNESP] (2014)
The Jundiá (Leiarius marmoratus) is a siluriform fish of the family Pimelodidae with reproductive migration during the rainy season, which occur in the basins of the Amazon and Orinoco rivers. It is a species of great economic value for its favorable husbandry characteristics, as little cannibalism in hatchery phase and good acceptance of dry foods in adulthood. It may be a vulnerable species due to changes in habitat because its reofilic behavior in at least one stage of its life cycle. In this context, studies that provide an appropriate captive breeding and knowledge of the biology of early development of the species, are sorely needed, aiming to produce juveniles for aquaculture or to support conservation programs their populations. The present study aims to establish a protocol for captive breeding with two hormonal substances, crude carp pituitary extract (EHC) and Ovopel ® (OVO: mGnRHa + metoclopramide), and describe the development of embryos and growth of larvae L. marmoratus. To establish the induction and reproduction protocols, males and females were selected based on observing external characteristics indicative of reproductive maturity, as bulging belly in females and emission of semen in males. Males were injected with OVO in total dosage of 2.5 mg.kg-1. In females, two inducing substances were tested: one group was injected in total dosage of 5.5 mg.kg-1 EHC and a second group was injected in total dosage of 5.5 mg.kg-1 of OVO. Females responded with oocytes elimination with 175.9 and 177.2 hours-degree for EHC and OVO at an average water temperature of 25.5 ± 8.8 ° C (p> 0,05). The diameter of ovulated oocytes was 665 ± 3.11 μm. Reproductive parameters such as the total and relative fecundity, and fertility were the same for both inducing substances (p> 0.05), with values of 612,000 and 605,400 oocytes.female-1 (fecundity), 125,800 and 132,000 oocytes.kg-1 body weight of the female (fecundity on weight) and 74.7 ...